Strategic Behavior of Companies for Prosperity in Dynamic Environments: An Empirical Study - Maja DARABOŠ LONGIN (Communications of International Proceedings, 2023)
Competitive dynamics is a phenomenon that is becoming more evident in many industries, even in those that were considered relatively stable until recently. Theoretical approach of competitive dynamics shows that relationship between firm´s strategy and firm performance primarily depends on firm strategic behavior, but also on competitors´ behavior and interactions between them. The goal of this paper is to theoretically and empirically indicate the relationship between firms’ strategic pattern – certain behavior and gaining competitive advantage in hypercompetitive industries. Even though a growing number of empirical studies dealing with the issue of achieving and maintaining competitive advantage in dynamic environments could be seen, they were primarily focused towards analyzing competitive dynamics and its impact on the financial performance of the firms. Thus, the main intention of this paper is to define and examine the link between firms’ strategic behavior in dynamic environment and achieving competitive advantage that could be indicated not only through financial performance indicators but also through some particular indicators of firm performance compared to the largest rival. Research results showed that there is positive connection between higher level of firm agility and firm strategic innovation, and superior profitability of the firm. In other words, firm characteristics that increase firm aggressiveness, i.e. firm agility and firm strategic innovation, represent a significant predictor and are crucial firm’s behavior in the dynamic environments if the firms are to survive, prosper and retain the competitive advantage.
Keywords: strategic patterns; firm strategic innovation; firm agility; temporary competitive advantage